Comparative Efficacy of Occlusal Splint Therapy and Conservative Physiotherapy in the Treatment of Temporomandibular Joint Pain: A Longitudinal Study: Occlusal Splint Therapy and Conservative Physiotherapy in the Treatment of TMJ Pain - Nawaz, Muhammad Shoaib; Haseeb, Muhammad; Hassan, Muhammad; Sadiq, Mukadas; Zulfiqar, Sadia; Shafiq, Samia (Pakistan Journal of Health Sciences, 2025)
Temporomandibular joint disorders significantly impact patients’ quality of life. Occlusal splint therapy and conservative physiotherapy (Transcutaneous Electrical Nerve Stimulation (TENS) and Electrical Muscle Stimulation (EMS)) are common treatments for temporomandibular joint disorders. However, their comparative long-term efficacy remains unclear. Objectives: To compare the efficacy of occlusal splint therapy and conservative physiotherapy (TENS and EMS) in improving mouth opening and reducing pain in temporomandibular joint disorder patients over six months. Methods: A longitudinal quasi study of 12 months was conducted with 112 patients randomly assigned to occlusal splint therapy (n=56) or conservative physiotherapy (n=56). Pre-operative and post-operative mouth opening and Visual Analog Scale (VAS) pain intensity scores were measured at 3 weeks, 6 weeks, 12 weeks, and 6 months. Independent sample t-tests and repeated measures Analysis of Variance (ANOVA) were used for statistical analysis. Results: Both groups showed significant improvements in mouth opening and visual analogue scale scores over time. The occlusal splint group demonstrated superior long-term outcomes, with greater improvements in mouth opening and pain reduction at 12 weeks and 6 months. RM-ANOVA revealed significant time effects for both treatments. Conclusions: It was concluded that occlusal splint therapy provides greater long-term improvement in mouth opening and pain reduction compared to TENS and EMS. These findings suggest the importance of considering treatment duration and follow-up in managing temporomandibular joint disorders.